Financial Feasibility of Business on Toy Startup: A Case Study of Cody Kit - Jagatpati, Thomas Aquinas Ardi; Irawan, Atika (Proceedings International Conference on Education Innovation and Social Science, 2023)
Coding and computer science has been a hot topic lately, and according to OECD estimates, approximately 10 billion jobs around the world are likely to be transformed by technology in the next decade. Coding and computer science are nominated as the essence of our future, as we are slowly arriving to an era where technology is a daily part of most of our lives. In spite of that, 825 million children worldwide are still not learning the skill they essentially need, including computer science. Cody Kit is a startup company who will become the answer to the problems. Cody Kit is a startup company which innovates a coding-based learning toy that integrates physical products with programming systems based on visual block games. The kit is concepted as an educational product that applied a step-by-step and coding-based learning method. However, Cody Kit hasn't done a financial feasibility study. The purpose of this research is to conduct a financial feasibility study for the development of Cody Kit where it uses a quantitative approach with company data as primary data and similar company data as secondary data. The financial feasibility will be analyzed by calculating the payback period, net present value (NPV), and the internal rate of return (IRR) then the risk will be assessed using scenario analysis. The results show that Cody Kit is financially feasible with a payback period of 2.821 years, with NPV of Rp21,175,355, and an IRR of 16.05% which is far greater than the WACC, which is 9.29%.